Decomposition of roots and nodules of centrosema pubescens benth - Hashim, Azizah (1979)
A modified technique involving incubation of moistened Serdang Series soil samples with segments of radicle and lateral roots as well as portions of nodules of Centrosema was used to study release of nitrogen into the soil as well as the biology of decompositon of roots and nodules of this legume. The samples were incubated for various lengths of time under optimum temperature and moisture content. At weeks 0, 1, 2, 4 , 8, 12 and 16, the respective soil samples were cleared of undecomposed legume tissues and analysed for total N, ammonium, nitrate, organic carbon and soil pH. At the same time the extracted laterals, radicle and nodule tissues were respectively plated on Czapek-Dox and potato dextrose agar media for isolation and enumeration of the decomposer mycoflora. The amount of ammonium nitrogen released from the different soil treatments was much higher than the levels of nitrate nitrogen released throughout the experiment. This could probably be due to the slightly acidic nature of the soil media used. The organic carbon content however decreased with increase in incubation time. This ultimately reSUlted in the narrowing of the C/N ratio to < 10 for all treatments under study. Accumulation of the ammonium nitrogen in the soil apparently resulted in the slight increase in soil pH. Soils amended with nodules varied significantly for all analyses when compared to the other treatments. The number of decomposer mycoflora isolated from the three tissue types increased with advanced tissue decay. For all the three tissue types used: laterals, radicles and nodules, five fungal genera were isolated frequently throughout the sampling period. The different gen era isolated were Fusarium, Trichoderma, Curvularia, Gliocladium and Penicillium. Total number of fungal genera and total isolates from decaying nodules were significantly higher when compared to results obtained from either decaying laterals or radicles.